1995
DOI: 10.1029/95eo00046
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient‐enhanced coastal ocean productivity explored in the Gulf of Mexico

Abstract: Nutrient enrichment from anthropogenic sources is one of the major stresses imposed on our coastal ecosystems. This is particularly true in the northern Gulf of Mexico where the nation's largest river discharges into an otherwise oligotrophic subtropical system. To better understand coastal ecosystem response to nutrient enrichment, 30 federal and academic scientists joined forces from 1989 to 1994 in an interdisciplinary investigation of the continental shelf of the northern Gulf of Mexico. Through the Nutrie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Discharge of freshwater and its dissolved and particulate constituents affect broad areas of the northern Gulf of Mexico (Ortner & Dagg 1995). According to the conceptual model of Dagg & Breed (2003), conditions for phytoplankton growth in the lower river are poor because of high concentrations of suspended sediments, but immediately after discharge and formation of a surface plume, the settling of large lithogenic particles results in a greatly improved light environment.…”
Section: Planktonic Community Structure In the Plumementioning
confidence: 99%
“…Discharge of freshwater and its dissolved and particulate constituents affect broad areas of the northern Gulf of Mexico (Ortner & Dagg 1995). According to the conceptual model of Dagg & Breed (2003), conditions for phytoplankton growth in the lower river are poor because of high concentrations of suspended sediments, but immediately after discharge and formation of a surface plume, the settling of large lithogenic particles results in a greatly improved light environment.…”
Section: Planktonic Community Structure In the Plumementioning
confidence: 99%
“…Light limitation due to turbidity is responsible for a lag in primary production away from the river mouth (Randall & Day, 1987;Lohrenz et ai., 1990). Peak nutrient utilization by phytoplankton (Lohrenz et ai., 1990) and subsequent secondary production (Dagg, 1995;Ortner & Dagg, 1995) occurs well downstream of the discharge point. This is typically toward the west along the Louisiana shelf (Wiseman & Garvine, 1995).…”
Section: Increased Trophic Transfer To Jellyfish: Effects Of Coastal mentioning
confidence: 99%
“…The greatest seasonal primary production rates in the northern Gulf of Mexico are associated with the Mississippi-Atchafalya River system and Mobile Bay estuary outflows; productivity rates are depressed accordingly with the lower-discharge estuaries of Texas (reviewed in Pennock et a!., 1999). Zooplankton grazing and secondary production are intense at the coastal transition zone (Dagg & Whitledge, 1991;Dagg, 1995;Ortner & Dagg, 1995) and trophic transfer of this energy to fish is highly coupled to estuarine delivery in the Gulf (Deegan et a!., 1986). The alternate pathway of energy to gelatinous zooplankton predators has thus far received little, if any, attention.…”
Section: Introductionmentioning
confidence: 99%
“…This entrainedlow-salinit:ywater can be rich in nutrients and contributes to enhanced productivity along the outer shelf, particularly west of the delta. Ortner and Dagg (1995) and Lohrenz et al (1990Lohrenz et al ( , 1999 reported high levels of phytoplankton production, occasionally greater that 8 g·C·m-2·d-1 in the river plume, especially after the settling of suspended matter allowed deeper light penetration. High chlorophyll a concentrations associated with the Mississippi River plume east of the delta have been reported by Hu et al (2003).…”
mentioning
confidence: 94%